Surfing's grand irony: the lack of awareness surrounding environmental degradation caused by the surf industry - Eddy, Nicole (The IIE, 2016)
The purpose of this study is to determine whether surfers are aware of the impacts that the surf industry has on the environment as well as to uncover the reasons for the disconnect between surfers who as a community self-identify as being ecologically aware, and their increased consumption of environmentally unfriendly surf gear. The research will look into the power that surf media and advertisements have on consumers and the effects that this is having on the environment through promoting increased surf tourism and surfboard production. This will lead to a deeper understanding of why surfers, who are regarded by themselves and by others as custodians of the sea, do not exude the environmental actions associated with this title within their regular lifestyles. A qualitative study was used investigating surfers’ environmental knowledge of the surf industry and their environmental actions. The research tool used for the study was an online questionnaire distributed to 50 surfers within Cape Town with each question being thoroughly analysed thereafter. The findings show that surfers within Cape Town are largely unaware of the impact that the surf industry has on the environment which has been predominantly due to the lack of information about the subject on mainstream surf media. It was also found that surf advertisements reinforce the surf ‘paradise’ discourses discussed within the study therefore promoting the surfer’s quest to find the perfect wave through long-distance traveling and investing into lighter and faster boards therefore increasing surf tourism and consumption to which have both detrimental social and environmental effects. The findings have also shown that there is a clear disconnect between surfers, who regard themselves as environmentalists and the environmental actions taken within their regular lifestyle.
THESIS
Keywords: Surfers; Surf industry; Surfers environmental knowledge; Surf media; Cape Town